2023
DOI: 10.3390/microorganisms11051304
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Characterization of Aeromonas veronii from Chinese Soft-Shelled Turtle (Trionyx sinensis)

Abstract: Aeromonas veronii is widespread in aquatic environments and is capable of infecting various aquatic organisms. A. veronii infection is lethal for Chinese soft-shelled turtles (Trionyx sinensis, CSST). We isolated a gram-negative bacterium from the liver of diseased CSSTs, which was named XC-1908. This isolate was identified as A. veronii based on its morphological and biochemical characteristics, and 16S rRNA gene sequence analysis. A. veronii was pathogenic for CSSTs with an LD50 of 4.17 × 105 CFU/g. The symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…eBURST analysis revealed the formation of one clonal complex (ST1027, ST1047), and the observed high nucleotide diversity suggested that most strains possessed unique sequence types, indicating a high level of genetic diversity. It is important to note that although MLST can provide valuable insights into the clonal relationships among bacterial strains, it may only capture part of the complexity of their evolutionary history [13,67]. Finally, recombination event analysis using RDP5 and Clonal-FrameML software detected 42 and 49 recombination events, respectively, with 22 results validated by four or more algorithms.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…eBURST analysis revealed the formation of one clonal complex (ST1027, ST1047), and the observed high nucleotide diversity suggested that most strains possessed unique sequence types, indicating a high level of genetic diversity. It is important to note that although MLST can provide valuable insights into the clonal relationships among bacterial strains, it may only capture part of the complexity of their evolutionary history [13,67]. Finally, recombination event analysis using RDP5 and Clonal-FrameML software detected 42 and 49 recombination events, respectively, with 22 results validated by four or more algorithms.…”
Section: Plos Onementioning
confidence: 99%
“…have increased, including A. hydrophila, A. sobria, A. veronii and A. caviae [10]. In particular, A. hydrophila and A. veronii cause hemorrhagic diseases in farmed fish, widely infect aquatic animals, and quickly become the epicenter of epidemic outbreaks, resulting in significant economic losses in aquaculture [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The sample was then placed at 4°C for 5 h and centrifuged at 4° for 10 min at 2500 rpm, and the supernatant was transferred to new Eppendorf tubes. Total protein (TP), albumin (ALB), globulin (GLB), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (AKP) activities in the serum samples were accomplished using a fully automated biochemical analyser (Sysmex) (Hu et al, 2023;.…”
Section: Serum Biochemical Indicesmentioning
confidence: 99%
“…TP, ALB, and GLB levels decreased in the serum of P. sinensis infected with Aeromonas veronii, whereas AST and ALT levels increased (Hu et al, 2023). TP, ALB, AKP, and GLB levels were decreased in this study (p < 0.05).…”
Section: Reports Have Indicated That C Indologenes Caused Septicaemia Inmentioning
confidence: 99%
“…Chinese soft‐shell turtle farming is associated with many infectious diseases during superintensive aquaculture growth (Zhou et al., 2008), including viruses, bacteria (Yuan et al., 2020) and fungi (Takuma et al., 2011), causing severe losses in this industry. These diseases are mainly caused by bacteria, such as Aeromonas hydrophila (Lin et al., 2014; Wu, 2004), Aeromonas caviae (Wu, 2004; Yu & Ma, 1997), Aeromonas sobria (Wu, 2004), Edwardsiella tarda (Pan et al., 2010), Lactococcus garvieae (Hu et al., 2010), Citrobacter freundii (Tang et al., 2023), Morganella morganii (Wei et al., 2023), Bacillus thuringiensis (Chen et al., 2014) and Bacillus cereus (Yuan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%